The RADAN series of compact pulsed power Generators and their applications; Proceedings of the IEEE; Vol. 92, iss. 7 - Mesyats G. A. Gennady Andreyevich; Korovin S. D.; Rostov V. V.; Shpak V. G.; Yalandin M. I. (2004, 2004)
В фонде НТБ ТПУ отсутствует